2015
DOI: 10.1016/j.neuron.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Hippocampal-Based Memory Requires Protein Synthesis Mediated by the Prion-like Protein CPEB3

Abstract: Consolidation of long-term memories depends on de novo protein synthesis. Several translational regulators have been identified, and their contribution to the formation of memory has been assessed in the mouse hippocampus. None of them, however, has been implicated in the persistence of memory. Although persistence is a key feature of long-term memory, how this occurs, despite the rapid turnover of its molecular substrates, is poorly understood. Here we find that both memory storage and its underlying synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
236
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(251 citation statements)
references
References 52 publications
15
236
0
Order By: Relevance
“…Uba2 is of a specific interest, acting as E1 ligase for SUMO 1-3 version of the protein degradation system (104,105). Strong reduction of Uba2 expression accords well with the recent findings demonstrating reduction of SUMOyation of aggregated CPEB3, a prion-like protein, which promotes protein synthesis leading to maintenance of LTP and consolidation of long-term memory (106,107). The role of CREB SUMOylation has been established in maintenance of long-term spatial memory (108).…”
Section: Discussionsupporting
confidence: 82%
“…Uba2 is of a specific interest, acting as E1 ligase for SUMO 1-3 version of the protein degradation system (104,105). Strong reduction of Uba2 expression accords well with the recent findings demonstrating reduction of SUMOyation of aggregated CPEB3, a prion-like protein, which promotes protein synthesis leading to maintenance of LTP and consolidation of long-term memory (106,107). The role of CREB SUMOylation has been established in maintenance of long-term spatial memory (108).…”
Section: Discussionsupporting
confidence: 82%
“…Fioriti et al (2015) found that in the basal state CPEB3 binds to and represses the translation of its target mRNAs in the brain, such as the a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunits GluA1 and GluA2 (Huang . Together, these data suggest that CPEB3 can act as a repressor in the basal state and can be converted to an activator in aggregation by posttranslational modification.…”
Section: The Role For Cpeb3 Aggregates In Local Protein Synthesismentioning
confidence: 99%
“…169 Finally, three recent manuscripts analyzed aggregation and self-perpetuation of the mouse ortholog of ApCPEB, CPEB3. 59,162,163 Studies of an ectopically expressed purified protein confirmed the ability of CPEB3 to form typical amyloid fibers with a characteristic birefringence upon Congo Red staining. Studies in yeast established that CPEB3 can act as a bona fide prion, i.e.…”
mentioning
confidence: 82%
“…Remarkable examples of the translation-coupled functional amyloids in multicellular organisms are neuron-specific forms of the cytoplasmic polyadenylation element binding protein (CPEB), ApCPEB, Orb2, and CPEB3 in the mollusk Aplysia californica, 24,159,160 fruit fly Drosophila melanogaster, 161 and mouse, 59,162,163 correspondingly. CPEB represents a family of RNA-binding proteins that bind U-rich sequences called CPE elements, which are located in the 3 0 untranslated regions of a number of cellular mRNAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation